2017
DOI: 10.1007/978-3-319-60855-6_12
|View full text |Cite
|
Sign up to set email alerts
|

Translational Regulation in the Mammalian Oocyte

Abstract: Fully grown oocytes arrest meiosis at prophase I and deposit maternal RNAs. A subset of maternal transcripts is stored in a dormant state in the oocyte, and the timely driven translation of specific mRNAs guides meiotic progression, the oocyte-embryo transition, and early embryo development. In the absence of transcription, the regulation of gene expression in oocytes is controlled almost exclusively at the level of transcriptome and proteome stabilization and at the level of protein synthesis.This chapter foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 246 publications
0
32
0
Order By: Relevance
“…Taken together, mTOR involvement is indispensable for inactivation of translational repressor 4E-BP1, which prevents the synthesis of essential proteins necessary for a correct completion of the meiotic and mitotic divisions. In addition to translational initiation factors, Ribosomal protein S3 (RPS3) is present at the mitotic 72 or newly forming meiotic spindle 73 . RPS3 knockdown causes arrest in mitotic metaphase, 72 which resembles the effect of mTOR inhibition 23 in the bovine oocyte.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, mTOR involvement is indispensable for inactivation of translational repressor 4E-BP1, which prevents the synthesis of essential proteins necessary for a correct completion of the meiotic and mitotic divisions. In addition to translational initiation factors, Ribosomal protein S3 (RPS3) is present at the mitotic 72 or newly forming meiotic spindle 73 . RPS3 knockdown causes arrest in mitotic metaphase, 72 which resembles the effect of mTOR inhibition 23 in the bovine oocyte.…”
Section: Resultsmentioning
confidence: 99%
“…However, according to the P/NP ratio of EDTA-treated NEBD-stage oocyte, we could not confirm or exclude the possibility that there were no high-molecular-weight stored ribonucleoprotein particles (RNP) that co-sedimented with polysomes and thus contained both rRNA species. It has been shown that maternal RNPs are stored in distinct sub-cellular regions in the oocyte [36]. Indeed, microscopic studies have revealed RNP aggregates at the cortex and in fibrillar cytoplasmic lattices and the latter of which also contains inactive ribosomes [36,57].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that maternal RNPs are stored in distinct sub-cellular regions in the oocyte [36]. Indeed, microscopic studies have revealed RNP aggregates at the cortex and in fibrillar cytoplasmic lattices and the latter of which also contains inactive ribosomes [36,57]. However, very little is known about their physical properties, complete protein composition nor their velocity sedimentation coefficients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The developmental processes, which include meiotic progression, oocyte to embryo transition, later spermatogenesis and early embryogenesis, require timely and strictly regulated transcriptional and translational control (Braun, ; Susor & Kubelka, ). For this purpose, newly transcribed precursor (pre)‐messenger RNAs (mRNAs) in the nucleus undergo a number of modifications such as capping, polyadenylation, and splicing in the germ cells and early embryos as is observed in eukaryotic cells (Barckmann & Simonelig, ; Piccioni, Zappavigna, & Verrotti, ).…”
Section: From Transcription To Translation In the Germ Cells And Earlmentioning
confidence: 99%